Transformasi Koperasi Simpan Pinjam (KSP) Menjadi Koperasi Simpan Pinjam Prinsip Syariah - Yunimar; Adi Prawira; Nasfi; Zakaria Aziz; Ahmad Lutri (Jurnal Pengabdian Masyarakat Akademisi, 2022)
Abstract The purpose of this activity is to assist each Cooperative that has been appointed by the Padang Panjang Koperindag Service in solving administrative problems, stabilizing the AD/ART of Sharia Cooperatives to Compiling Financial Reports for Sharia Cooperatives. The method used is the root cause method, using awareness, capacity building and empowerment strategies. As a result of this cooperative assistance, all cooperatives that have been assisted are all ready and willing to seriously convert their cooperatives into sharia cooperatives. So there are about 6 (six) cooperatives that are sharia legal and apply sharia principles from a total of 42 (forty two) cooperatives that are assisted and there are 36 (thirty six) cooperatives that are legally not Sharia cooperatives.